Maximizing Developmental Potential and Parenting Patterns in the Married Couples Community of GKI Gejayan Yogyakarta - Anggreany, Yuliana; Helsa; Theresia , Allessandra; Rani Lidiawati, Krishervina; Aurelia, Trisha (Devotion : Jurnal Pengabdian Psikologi, 2025)
An understanding of parenting has becoming increasingly important, especially within church communities. GKI Gejayan recognizes the significance of parenting in supporting the growth of children and adolescents in a Christian context. This understanding led to developing a community service program titled, "Maximizing Developmental Potential and Parenting Patterns within the GKI Gejayan Yogyakarta Spouse Community”. The program uses a psychoeducational approach with two main sessions aimed at equipping parents with practical tools for better parenting. The first session, held in person, focused on child development, covering cognitive, physical, and psychosocial aspects that influence parenting. It also addressed common parenting challenges and introduced love languages, providing parents with strategies to improve their parenting methods. The second online session concentrated on the role of discipline in child-rearing, exploring effective disciplinary methods and the appropriate use of punishment to support child development. The program targets married couples with children, offering valuable guidance to help them support their children's growth at each developmental stage. Ultimately, this initiative seeks to enhance parenting practices and contribute to the holistic development of children and adolescents in the community.